Micropropagation of Pelargonium odoratissimum (L.) L’Her. through petioles and leaves - Ebrahimzadeh, Asghar; Fathollahzadeh, Maliheh; Bagher Hassanpouraghdam, Mohammad; Aazami Mavaloo, Mohammad Ali (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2021)
Pelargonium odoratissimum (L.) L’Her is a hard rooting plant and the common methods of propagation via stem cuttings are not successful with this species. therefore, tissue culture methods have been experienced for the mass-propagation of this high-valued species. Intact leaves, leaf segments and petiole sections derived from nodal explants in vitro were employed for the optimization of P. odoratissimum micropropagation. The treatment combinations used were MS and 1/2 MS media supplemented with 6-benzylaminopurine, BAP (1, 1.5, 2 and 4.5 mg.L-1) and 1-naphthaleneacetic acid, NAA (0.1, 1 and 1.5 mg.L-1). With leaf segments, the lowest browning incidence, the greatest callogenesis and the highest number of shoots were obtained with the media containing 1.5 mg.L-1 BAP and 1 mg.L-1 NAA. Two mg.L-1 BAP + 0.1 mg.L-1 NAA kept the same results for petiole explants. Intact leaves showed the best results for the three mentioned treatments with 1 mg.L-1 BAP + 1 mg.L-1 NAA. 0.2 mg.L-1 NAA caused the highest rooting percentage and the greatest mean data for the number and length of the roots. Rooted plantlets were transferred to the pots containing 1:1 peat-moss and perlite. Acclimatization of the plantlets was followed by 90 % of survival rate in the greenhouse. The protocol employed would be a potent one to present for the extension section.